Contemporary conditional cancer‐specific survival after radical nephroureterectomy in patients with nonmetastatic urothelial carcinoma of upper urinary tract. Issue 7 (27th February 2020) - Rosiello, Giuseppe; Palumbo, Carlotta; Knipper, Sophie; Pecoraro, Angela; Luzzago, Stefano; Deuker, Marina; Mistretta, Francesco A.; Tian, Zhe; Fossati, Nicola; Gallina, Andrea; Montorsi, Francesco; Shariat, Shahrokh F.; et al.
Abstract: Background and Objectives: To examine the effect of conditional survival on 5‐year cancer‐specific survival (CSS) probability after radical nephroureterectomy (RNU) in a contemporary cohort of patients with non‐metastatic urothelial carcinoma of the upper urinary tract (UTUC). Methods: Within the Surveillance, Epidemiology and End Results database (2004‐2015), 6826 patients were identified. Conditional 5‐year CSS estimates were assessed after event‐free follow‐up duration. Multivariable Cox regression (MCR) models predicted cancer‐specific mortality (CSM) according to event‐free follow‐up length. Results: Overall, 956 (14.0%) were T1 low grade(LG)N0, 1305 (19.1%) T1 high grade(HG)N0, 1215 (17.8%) T2 N0, 2249 (32.9%) T3 N0 and 1101 (16.1%) T4 N0 /Tany N1‐3 . From baseline, 93.4% to 94.2% in T1 LGN0 provided 5‐year CSS and, respectively, 86.2% to 95.3% in T1 HGN0, 77.5% to 87.8% in T2 N0, 63.0% to 91.1% in T3 N0, and 38.8% to 88.2% in T4 N0 /Tany N1‐3 . In MCR models, relative to T1 LGN0, T1 HGN0 (Hazard ratio [HR] 1.7), T2 N0 (HR 3.0), T3 N0 (HR: 5.2), and T4 N0 /Tany N1‐3 (HR 11.9) were independent predictors of higher CSM. Conditional HRs decreased to levels equivalent to T1 LGN0 at 3 years vs 5 years of event‐free survival for T1 HGN0 and all other groups, respectively. Conclusions: A direct relationship exists between event‐free follow‐up and survival probability after RNU. From a clinical perspective, such survival estimates may have particular importance during preoperative counseling.